Pengaruh Lingkungan Kerja Dan Stres Kerja Terhadap Kepuasan Kerja Karyawan Pabrik Gula Pesantren Baru Kediri - Muhammad Hafidh; Mahfudiyanto (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2021)
Sugar factory Pesantren Baru Kediri is a company engaged in the sugar industry engaged in sugar cane milling (sugar manufacture) which is the locomotive of the regional and national economy. This study aims to determine the effect of work environment and work stress on employee job satisfaction at PG Pesantren Baru Kediri. This research method is a quantitative method with a causal approach. Data collection techniques using questionnaires that have been tested using data quality tests, classical assumption tests and multiple linear regression analysis. The population in this study were all permanent employees at PG. Pesantren Baru Kediri, amounting to 195 employees.The sample in this study amounted to 13 employees who were determined using simple random sampling technique using the sample size formula Sugiyono (2017) The results showed that (1) The work environment has a partial effect on employee job satisfaction (2) Job stress has a partial effect on satisfaction Employee work (3) Work environment and work stress simultaneously affect employee job satisfaction at PG Pesantren Baru Kediri. Keywords: Working Environment; Job Stress; Job Satisfaction